Macular Inner Retinal Layer Thickness in Relation to Photopic and Mesopic Contrast Sensitivity in Healthy Young and Older Subjects - Puell, María Cinta; Palomo-Álvarez, Catalina; Pérez-Carrasco, María Jesús (Investigative ophthalmology & visual science, 2018)
To examine relationships between the thicknesses of ganglion cell (GC)-related macular layers and central photopic or mesopic contrast sensitivity (CS) in healthy eyes. Measurements were made in 38 young and 38 older healthy individuals. Total, inner, and outer retinal layer (IRL) thicknesses were measured in the macula region through spectral-domain optical coherence tomography (SD-OCT) across three subfields, or rings, centered at the fovea: central foveal, pericentral, and peripheral. Ganglion cell complex and circumpapillary retinal nerve fiber layer thicknesses were also measured. Low-spatial-frequency CS for gratings presented at the central 10° visual field were measured through computerized psychophysical tests under photopic and mesopic conditions. Relationships were examined by uni- and multivariate regression analysis. Peripheral IRL thickness emerged as the only independent predictor of photopic CS (P = 0.001) in the young group and of photopic (P = 0.026) and mesopic CS (P = 0.001) in the older group. The slopes of regression lines used to predict CS from peripheral IRL thickness were significantly different for pair-wise comparisons of both photopic CS and age group (P = 0.0001) and mesopic CS (P = 0.0001) and age group. These models explained 37% of the variability in photopic CS and 36% of the variability in mesopic CS. Macular IRL thinning likely due to GC loss was related to reduced photopic and mesopic CS in older healthy eyes. In contrast, in the young eyes, a thicker macular IRL, possibly indicating transient gliosis, was associated with reduced CS.